Implantation of the analogue visual scale of pain in a low complexity ambulatory of a Higher Education Institution (Research, Society and Development, 2018)
The goal of this study is to implement the visual analogical pain scale in a low complexity ambulatory of a higher education institution in all the nursing attendances. This is a descriptive and prospective study, with qualitative analysis, which were interviewed the six professionals who work in the mentioned local. It were verified, that the pain control and relief are responsibilities and compromise of the professional from health area, therefore, between the interviewees it was clear the importance to the assistance and standardization of the attendances. It is necessary to accomplish the implementation of the visual analogical pain scale for a patient integral care, pain management and control, immediate intervention and subsequent revaluations, as well as to monitor the patient development in relation of the treatment.